A hesitant fuzzy cognitive mapping approach with risk preferences for student accommodation problems. (2017) - Ghaderi, H.; Gitinavard, H.; Mousavi, S. Meysam; Vahdani, Behnam
In this paper, a new fuzzy cognitive mapping approach is proposed, in which the values of the concepts and the strength of the links are presented through a set of possible values under hesitant fuzzy sets (HFSs). In particular, we discuss student accommodation problems which can occur at every education system and affect students' academic achievements. In this regard, we interview with the university chancellor, the student accommodation manager, and the top student to create individual cognitive maps; then, these cognitive maps aggregate to build the strategic cognitive map. In this study, based on the experts' opinions, three kinds of scenarios, optimistic, moderate, and pessimistic, are developed. By so doing, the concept with the most value is determined. Furthermore, the effects of different initial values of the concepts on the final values and the number of simulation iterations are analysed.